The specific distribution of unsaturated fatty acids in the triglycerides of plants - F.H. Mattson; R.A. Volpenhein (Journal of Lipid Research, 1963)
The distribution of fatty acids between the primary and the secondary positions of the triglyceride of 28 species of plants was determined. In confirmation of previous results, palmitic and stearic acids were found to be esterified predominantly at the primary positions. An earlier study demonstrated that fatty acids having a chain length of greater than 18 carbon atoms are also esterified predominantly at the primary positions. Examination of the data in the present and previous studies shows oleic, linoleic, and linolenic acids to have a common pattern of distribution. Each of these acids is approximately randomly distributed among the positions on the triglyceride molecule that are not occupied by palmitic or stearic acids or fatty acids having a chain length greater than 18 carbon atoms. The mechanisms by which these specific distributions could be brought about are discussed.